Análisis de la recaudación tributaria de los principales impuestos de la zona 6, periodo 2016-2020 - Torres Torres, Yuliza Yessenia (2022)
The curricular integration or qualification work called: ANALYSIS OF THE TAX COLLECTION OF THE MAIN TAXES OF ZONE 6, PERIOD 2016-2020, was carried out prior to obtaining the title of Bachelor of Accounting and Auditing, developed in accordance with the Regulation of Academic Regime of the National University of Loja, with the purpose of identifying the tax collection and knowing the contribution of Zone 6 to the General State Budget, considering that the collection of tax taxes is one of the income that contributes the most to the State. To carry out the analysis of the tax collection of Zone 6, a detailed study of the main taxes of Ecuador was carried out based on the compilation of theoretical and practical foundations, ordering the information from the general to the specific, the same ones that due to their great contribution to the General State Budget, its method of calculation and impact on the economy constitute an important support within the national context, not only in order to make a theoretical, legal, and conceptual description, but primarily to identify the collection of the Zone 6. The tax collection according to the data obtained from the Internal Revenue Service, allowed a comparison of the taxes of the provinces that make up Zone 6 during the years 2016 to 2020, observing that the province of Azuay is the one with the highest collection, with a total value of USD 3,201,016,275.40, followed by the province of Cañar with a total amount of USD 179,837,838.48 and the province of Morona Santiago with a total of USD 80,107,942.03. The taxes with the highest tax collection of the different provinces that make up Zone 6, using the representation of statistical tables and graphs, helped to know the values and their percentage variation, identifying that the taxes with the highest collection in the province of Azuay are: Value Added Tax, Income Tax, Special Consumption Tax and Foreign Currency Outflow Tax, while in the provinces of Cañar and Morona Santiago the taxes with the highest tax collection are: Income Tax, Tax Added Value, the Tax on Motor Vehicles and the Environmental Tax on Vehicle Pollution. Based on the information provided by the annual reports on the execution of the General State Budget and data from the Internal Revenue Service, it was observed that the contribution of the main tax taxes of Zone 6 to the General State Budget is as follows: Value Added Tax contributes with USD 1,739,389,783.72 which represents 5.95%, Income Tax with USD 984,672,991.39 which represents 4.95%, Special Consumption Tax with USD 312,615. 5 463.40, which represents 7.19%%, and the Foreign Currency Outflow Tax with USD 107,355,400.01, which represents 2.35%. Finally, the curricular or degree integration work issues suggestions focused on simplicity and legal certainty, the need for tax incentives for economic growth, training to strengthen the tax culture that allows contributing to voluntary compliance with tax obligations, reduce evasion and avoidance to achieve the necessary collection sufficiency and compliance with the purposes of the State, thinking of the national welfare.